Morphological differentiation of Peromyscus leucopus and P. maniculatus in East Texas - Light, Jessica E; Siciliano-Martina, Lelila; Dohlanik, Emma; Vielleux, Grace; Hafner, David; Lawing, A Michelle; Greenbaum, Ira (THERYA, 2021)
The white-footed deer mouse (Peromyscus leucopus) and the North American deer mouse (P. maniculatus) are widely distributed throughout North America, often with overlapping distributions. These species are believed to be sympatric east of the Balcones fault zone in Texas, but records from natural history collections indicate that P. maniculatus is not common from this region. Given that these two species are notoriously difficult to differentiate morphologically, it is possible that specimens have been incorrectly identified and that P. maniculatus may be rare or not present in East Texas. This study aims to determine if P. leucopus and P. maniculatus can be differentiated morphologically east of the Balcones fault zone in Texas. Cranial and external characters from genetically identified specimens representing each species were analyzed using traditional and geometric morphometric methods. Morphological analyses revealed that genetically identified specimens of P. leucopus and P. maniculatus from east of the Balcones fault zone could be differentiated using a suite of morphological characters. Many of the specimens of P. leucopus used in this study were originally misidentified, suggesting that P. maniculatus is rare in East Texas.